2011
DOI: 10.1159/000323932
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Class-I-Interacting Natural Killer Cell Receptors of Nonhuman Primates

Abstract: Human natural killer (NK) cell receptors are known to be highly polymorphic, to show complex genetics and to be associated with susceptibility to a variety of immunological diseases. Nonhuman primates are used as important models of these diseases, yet the knowledge of nonhuman primate NK cell receptors and ligands is not as advanced as in humans. Recently published data indicated that diversity and polymorphism of NK cell receptors are similar between nonhuman primates and humans. Comparative genomics reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Recent studies have suggested that adopted transfer of NK cells may be a promising therapeutic approach for cancer patients ( 4 7 ). The phenotypic and functional characteristics of NK cells have been documented in various species, including mice, rat, pigs, cows, and humans ( 8 11 ). Although the total population of human and mouse NK cells is phenotypically and functionally heterogeneous ( 12 , 13 ), expression of specific surface molecules, such as CD56 and CD16 on human cells, and NK1.1 and NKp46 on mouse NK cells, allows the identification of NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that adopted transfer of NK cells may be a promising therapeutic approach for cancer patients ( 4 7 ). The phenotypic and functional characteristics of NK cells have been documented in various species, including mice, rat, pigs, cows, and humans ( 8 11 ). Although the total population of human and mouse NK cells is phenotypically and functionally heterogeneous ( 12 , 13 ), expression of specific surface molecules, such as CD56 and CD16 on human cells, and NK1.1 and NKp46 on mouse NK cells, allows the identification of NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Killer cell immunoglobulin-like receptors (KIR) are crucial regulators of NK cell activity and exhibit considerable allelic polymorphism and copy-number variations in humans and higher primates ( 5 , 6 ). Epidemiological studies of human immunodeficiency virus 1 (HIV-1) infection indicate that a combination of HLA-Bw4-80I with either KIR3DL1 or KIR3DS1 is associated with delayed progression to AIDS ( 3 , 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Larger consortia that compile large -omics datasets for marmosets are being built [96,97]. For instance, functional genomics data from marmoset brain tissues have been collected and incorporated into the NIH Brain initiative [98]. This is of particular relevance as the common marmoset has been identified as an important model organism for neuroscience research that can bridge the gap between mice and humans [96,99].…”
Section: Callithrix Functional Genomics and Epigenomicsmentioning
confidence: 99%